Belgium : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
Belgium's impressive past fiscal consolidation is an example for other countries that need to bring down their public debt and also provides insights on how best to address its own current fiscal challenges. Belgium has a unique history of a long and successful large fiscal consolidation. Belgium lived through various episodes of fiscal adjustment and each one of these contains important lessons for future consolidation. After Belgium's public debt-to-GDP reached a peak of about 135 percent in 1993, it was steadily reduced to about 84 percent by 2007.